Common vetch (Vicia sativa) multi-podded mutants for enhanced commercial seed production - Aleksandar Mikić; Vojislav Mihailović; Đura Karagić; Branko Milošević; Dragan Milić; Sanja Vasiljević; Snežana Katanski; Dalibor Živanov (Труды по прикладной ботанике, генетике и селекции)
In comparison to other annual forage legumes, such as pea (Pisum sativum L.), advances in breeding vetches (Vicia spp.) are rather modest. One of the main obstacles in increasing the cultivation area under vetches is uncertain seed production, mostly due to their indeterminate stem growth and non-uniform maturity, with the genes controlling these important traits still unattested. In contrast, in wild populations of common vetch (V. sativa L.) the genes have been identified, isolated in this study, and mutant plants with more than usual two pods per node tested. Crossing these mutant genotypes with wild-type ones demonstrated that the number of pods in this vetch species is controlled by two genes, orthologs to FN and FNA in pea. If both genes are recessive, a plant will have more than two flowers per each node and, depending on not yet clarified environmental factors, more than two pods per node. Developing vetch cultivars with more than two pods per node may be one of the solutions for enhancing seed production in this crop.